Pengaruh Peran Sarana dan Prasarana terhadap Kualitas Pembelajaran Kelompok Bermain di PAUD Kristen Bait’El - Mita Sari; Felista Mohamad; Nida Tazkia Saleh; Putri Regina Sinubu; Mega Putri Ramadani; Tiara Baulu; Fauzia H Minura; Ainun Putri Pakaya; Nurhayati Polingala; Astiana S (Inovasi Pendidikan dan Anak Usia Dini, 2026)
Facilities and infrastructure play a crucial role in enhancing the quality of learning in Playgroup (Kelompok Bermain). This study aims to examine the influence of the availability and management of facilities and infrastructure on the effectiveness of early childhood learning processes. A quantitative research method was employed using surveys with questionnaires distributed to teachers and administrators of Playgroups. The collected data were analyzed through descriptive statistics and regression analysis to determine the relationship between facilities and infrastructure and learning quality. The findings indicate that adequate facilities such as comfortable classrooms and educational aids significantly improve children's learning motivation and the smoothness of the learning process. Well-equipped environments enable teachers to deliver lessons more effectively, thus positively impacting children's learning outcomes. In conclusion, improving and maintaining facilities and infrastructure should be a priority for Playgroup managers to ensure optimal learning quality and support the holistic development of young children.